Control over Coastal Sedimentation Land by the Indonesian Household Migrant Workers - Septianto, Marzuqo; M Kolopaking, Lala; Adiwibowo, Soeryo (Sodality: Jurnal Sosiologi Pedesaan, 2018)
This study aims to analyze: 1). power relations over land emerging that occurred in Sugihwaras. 2). Land institutional crisis that becomes the arena of mastery among actors in it, 3). the reason behind the interest of Indonesian Migrant Workers in exploiting land emerging in Sugihwaras. A qualitative approach is applied in this case and data collection is done using observation, interview, and documentation methods. The results show that the power relations of the land arise form the agrarian structure in the society where each actor has a boundary of power and boundle of right are different. The existing institutional land crises in the Community are described in chronological crises of land ownership by actors and their claims to land arising in Sugihwaras. Indonesian Migrant Workers become one of the important actors in relation to access to arising land, where they have access to funds used for land purchase, or building settlements on arising land.